Rancangan Aplikasi Berbasis Augmented Reality Dalam Pemeliharaan Front panel DME (Distance Measuring Equipment) Merek Thales Tipe 435 - Santhika Satria Ningrum, Erlina Dwi; Purwaningtyas, Dian Anggraini; -, Toni (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2024)
Distance Meaasuring Equipment (DME) is one of the flight navigation equipment that functions to provide distance guidance to the aircraft to the airport to be addressed. The condition of any equipment used in aviation needs to be ensured that it is always in a normal state by carrying out maintenance according to procedures. The high complexity and precision in maintenance can affect the ability to remember or cognitive load of a technician. The purpose of this research is to design DME maintenance procedures in the form of Augmented Reality applications to overcome the cognitive load of technicians so as to minimize human error and increase the effectiveness of maintenance activities. This research uses the prototype method to design Augmented Reality DME applications that suit user needs. The information displayed is an indicator check, measurement of supporting facilities and reading of DME parameter values. Users can access DME maintenance procedures through an android device. The results of the evaluation of the DME Augmented Reality application using Functional suitability testing found that all features or menus can operate properly without errors. Thus, this application can be used to assist technicians in improving the effectiveness of the Thales 435 Brand DME maintenance procedure.